Usefulness model for the redesign of Graduate’s Student Management Information System - Fanindia Purnama Sari,; Noraidah Sahari Ashaari, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Postgraduate Student Management Information System (PSMI) is developed for managing the academic matters of postgraduate students, such as registration, appointment of supervisor, proposal defence, appointment of examiners and managing oral defence examination. The system which is known as SMASH was developed in the Faculty of Information Science and Technology, Universiti Kebangsaan Malaysia to facilitate the task of the Graduate Management Unit. However, SMASH is rarely used due to usability problems. Among the problems are, the administrative staffs are not aware of the graduate programs applications which are made through SMASH. There is a lack of functionality especially on the menu and the design of the interface. SMASH provides functionality that is limited to only download the application form. This paper discusses the usefulness model development that can be used as a guideline to improve the system. The usefulness model is developed by adapting IS0 9241 and ISO 9126 usability standards. This study employs User-Centered Design method which involves students and faculty administrative staffs. This study starts by identifying the usability problems through Heuristic Evaluation and analysing the user requirements through the system analysis and interview. The preliminary study discovers that there is a need for improvement in the interface design and the functionality of the system to meet user requirements. The user requirement analysis and the proposed improvement serves as the basis in redesigning the system prototype. The usefulness model is then verified by 30 respondents through survey.